Cr(III) Removal from aqueous solutions by depectinated sugar beet pulp - Özer, Ahmet; Tümen, Fikret; Bildik, Memnune (My University, 1997)
We report a study of the removal of Cr(III) from aqueous solutions by depectinated sugar beet pulp (DSBP) carried out at different initial concentration of Cr(III), pH and temperature of solution, particle size and adsorbent dosage. Removal percentage of Cr(III) was found to be 86 for inital concentration of 10 mg L?1 at 20 °C and 20 g L?1 adsorbent dosage. The optimum pH for the process was found to be 4.5. The process of uptake follows first-order adsorption rate expression and obeys Langmuir and Freundlich's adsorption models. Enthalpy change of adsorption was found to be ?27.3 kJ mol?1. Little fraction of Cr(III) was desorbed in strong acidic media.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cr(III) removal; Sugar beet pulp; Thermodynamic parameters; Adsorption; Desorption